Bens em estoque: uma análise voltada à essencialidade no contexto da lei n. 11.101, de 9 de fevereiro de 2005 - Mello, Marcus Vinícius Ramon Soares de (2020)
This dissertation aims, mainly, the effectiveness of judicial reorganization, focusing the study on the essentiality of the assets in possession of company in judicial reorganization and the consequent possibility to apply this protection to the items in inventory. One of the most relevant discussions surrounding the Law n. 11.101/05 of February 9th, 2005, is the suspension of certain creditor’s right to sell and remove certain assets of the company in judicial reorganization during the “stay period”, in case this asset is considered essential for business activity. However, this law has adopted the expression “essential capital assets”. As a result, by literal analysis, some assets are not affected by the benefit granted by the legislator. Therefore, this dissertation presents a brief study of the history of the Law in force, its basic principles, the relationship with the current Federal Constitution, and also promotes research on the current interpretation of the exception of article 49, paragraph 3rd, final part, of the Law under examination. In view of what was proposed for this dissertation, it is also necessary to study the types of inventories and seek to relate to the essential, within the possibility. Thus, the study of doctrine — doctrine law and others — was used, as well as the federal and state jurisprudence. Therefore, the conclusion of this dissertation was that, if the intention is to proceed with the protection of essential assets that are not necessarily capital assets depending on the analysis, the items in inventory, provided that the nature, importance, quantity, incident, expenses, relevance is considered in billing, among other things to be observed, so they can be considered as essential assets at least for the company in judicial reorganization, given the impact of these assets on the business activity and recovery of the company in economic and financial crisis, even without ignoring sources recognizing the need for protection. However, such benefit should not be conferred indiscriminately and without observing creditor’s rights or specific inventory studies. Likewise, it does not seem appropriate that such overrun to the term “capital assets” continues to occur, in overcoming the legal text. This way, the ideal, as researched, would be to adapt the legal text to current demand